Peran Dalem Lenggana Bangkelung Bagi Kesultanan Mataram: Kajian Naskah Kuno dan Tradisi Lisan - Ahmad Rizky Fauzi; Rina Wahyunita (Badan Riset dan Inovasi Nasional (BRIN), 2023)
This study explains the role of Dalem Lenggana as a religious spreader of Islam as well as a blacksmith of the Mataram Sultanate, which originates from folklore, Dutch reports, and ancient manuscripts. The ancient manuscripts are the Sukawening Garut Manuscript and the Pegon manuscript which have been transliterated by K. F. Holle and published in his report. The two manuscripts tell of Dalem Lenggana's work which is set in the early Islamic period, to be precise, during the Mataram Sultanate. The name Dalem Lenggana has many versions of the name, but both texts refer to the figure Dalem Lenggana in Bangkelung, Galuh. the existence of Dalem Lenggana existed in the period 1645 AD – 1704 AD. He was appointed leader of the Bangkelung region after successfully making Guntur Geni guns (Cannons). Given the importance of Dalem Lenggana's role in the past, this is the background for the author to discuss it. This research method uses a qualitative approach with a descriptive type. Data collection techniques are carried out through observation, interviews, and document studies. In this study, the authors used primary and secondary data sources. The results showed that the Dalem Lenggana figure had an important role in the past both as a spreader of Islam, a blacksmith in the Mataram Sultanate and as a leader in the Bangkelung region of Galuh.